The use of new ICTs in trade union protests – five European cases. (August 2016) - Rego, Raquel; Sprenger, Wim; Kirov, Vassil; Thomson, Greg; Nunzio, Daniele Di
Despite the interest in the use of new information and communication technologies (ICTs) by trade unions, little is known about how new ICTs have changed trade union protest. In a period of austerity, in which new groups – including labour-related ones – have shown impressive mobilization using social media, we focus on a cross-country approach, looking at the impact of trade union strikes and protest in the public sector. Our findings show that new ICTs are being used at all stages of strike action and union protests in general, but do not allow us to assert that unions have changed the way they act in a fundamental way.